Empowering Cadres Through Education And Complementary Services: Biomassage In Increasing Body Immune Power In Hypertension Communities In Dauh Puri Kelod Village, West Denpasar Denpasar City - Labir, I Ketut; Ribek, Nyoman; Ruspawan, Dewa Made (Poltekkes Kemenkes Denpasar, 2025)
Background: Hypertension remains a major public health problem and contributes significantly to morbidity and mortality. In Denpasar City, the prevalence of hypertension is still high despite the availability of conventional medical services. Long-term pharmacological treatment often leads to low adherence, highlighting the need for complementary, community-based interventions to support hypertension control.Objective: This community service activity aimed to increase the knowledge of Posbindu cadres regarding biomassage and to assist cadres in providing complementary biomassage services to help reduce blood pressure among people with hypertension.Method: The activity involved cadre education and community-based biomassage services. A total of 45 Posbindu cadres participated in the training, while 142 community members received services, including 58 individuals with hypertension. Cadres’ knowledge was measured using pre-test and post-test assessments, and systolic blood pressure of hypertensive participants was measured before and after biomassage intervention. Data were analyzed using paired t-tests.Result: The results showed an increase in the average knowledge score of Posbindu cadres from 74.4 to 94 (p 0.05). Among hypertensive participants, the mean systolic blood pressure decreased from 148 mmHg before intervention to 126 mmHg after biomassage, with an average reduction of 22 mmHg (p 0.05).Conclusion: The activity demonstrated that biomassage education and services effectively improved cadres’ knowledge and contributed to a reduction in systolic blood pressure among people with hypertension. Biomassage may be used as a complementary approach to support community-based hypertension management alongside conventional treatment.